2003
DOI: 10.1097/01.mlr.0000065126.73750.d1
|View full text |Cite
|
Sign up to set email alerts
|

Late Stage Cancers in a Medicaid-insured Population

Abstract: Cancer patients enrolled in Medicaid after their diagnosis were disproportionately likely to have late stage disease relative to patients previously enrolled in Medicaid or non-Medicaid enrollees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 26 publications
6
62
0
Order By: Relevance
“…As noted earlier, the review of the literature points to a lack of consistency among researchers relative to whether to exclude unstaged cases from the analysis [18,19,20], to group unstaged cases with latestaged cancers [21,22], or even to analyze unstaged cases in a separate stage category [11,14,23,24]. SEER reports survival rates for unstaged cases that are somewhat more favorable than for those with distant stage cancer, but less favorable than for those with regional stage cancer [3,4,5], and a previous study has documented differences in survival patterns among unstaged cases when analysis was performed in age-specific strata [11].…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, the review of the literature points to a lack of consistency among researchers relative to whether to exclude unstaged cases from the analysis [18,19,20], to group unstaged cases with latestaged cancers [21,22], or even to analyze unstaged cases in a separate stage category [11,14,23,24]. SEER reports survival rates for unstaged cases that are somewhat more favorable than for those with distant stage cancer, but less favorable than for those with regional stage cancer [3,4,5], and a previous study has documented differences in survival patterns among unstaged cases when analysis was performed in age-specific strata [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing other types of cancer have also reported the existence of an inverse gradient between the length of previous Medicaid enrollment and the likelihood of advanced-stage disease. [9][10][11][12] Several studies have described associations between low SES and an increased likelihood of late-stage melanoma at diagnosis, and report that the effect of SES on late diagnosis operates independently of race/ethnicity. 2,6,8,[19][20][21][22] The results of the current study also showed a clear inverse gradient by neighborhood SES, with individuals living in lower-SES neighborhoods being significantly more likely to have late-stage melanoma at diagnosis than those in high-SES neighborhoods, even after covariate adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…A 1994 study of Florida melanoma patients found a four-fold higher risk of late stage at diagnosis for those covered by Medicaid compared to those with commercial indemnity insurance. 7 More-recent studies have reported associations between the status and duration of Medicaid enrollment and the late-stage diagnosis of breast, colorectal, pancreatic, and cervical cancers, [9][10][11][12] implying that people not enrolled in Medicaid or those enrolled for shorter periods prior to cancer diagnosis are at greatest risk for more-advanced cancer. These associations have not yet been examined for melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…The previously noted studies also could have been affected by a confounding effect; for example, newly diagnosed cancer patients enrolling in Medicaid were more likely at a later stage of disease than those enrolled prior to their diagnoses Bradley et al 2003), due again to the structure of Medicaid eligibility rules. Another advantage of linked registry and Medicaid files was that we were able to test the potential policy lag by expanding our test of the effect of the BCCPTA from the initial implementation month to up to a year afterward.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to qualify for Medicaid as a disabled person in Georgia, and indeed in most other states, a cancer patient would need a certification by a doctor indicating that she had a physical or mental impairment that was expected to last at least 12 months (Benítez-Silva et al 1999;Benitez-Silva et al 2004) and had income generally less than 75% FPL (Kaiser Commission on Medicaid and the Uninsured 2010). Generally speaking, this aspect of Medicaid criteria makes the disabled wait long periods for eligibility and may help explain why Medicaid patients are more likely to be diagnosed at a late stage (Bradley et al 2003;Bradley et al 2005). In addition, unlike the situation with the BCCPTA, other eligibility groups in many states deal with a long and cumbersome process that requires applicants to locate different documentation necessary to verify the value of their resources.…”
Section: Introductionmentioning
confidence: 99%